Rehabilitation with intensive attention training early after acquired brain injury promotes better long-term status on health-related quality of life, daily activities, work ability and return to work - Gabriela Markovic; Aniko Bartfai; Marie-Louise Schult; Jan Ekholm (Medical Journals Sweden, 2024)
Objective: To describe long-term effects on activity, participation, and quality of life (i) at different post-injury starting time points of attention training and (ii) of two different types of rehabilitation with attention training in patients after stroke or traumatic brain injury; and to describe their functioning level. Design: 2 years after rehabilitation intervention, comparisons were made in one cohort receiving attention training subacute (< 4 months) or post-acute (4-12 months) and in one cohort with two different training methods, a process-based and an activity-based method respectively. Patients: 100 patients were recruited from our earlier RCT study. They had mild to moderate stroke or traumatic brain injury with relatively limited symptomatology, and all had moderate to severe attention impairment. Methods: A questionnaire-based interview: EuroQol 5 dimensions, Occupational Gaps Questionnaire, Work Ability Index, self-assessed work status, self-reported employment conditions, sick leave, and experienced cognitive limitations in work performance. Results: An advantage for patients receiving subacute attention training regarding daily activities, work ability and returning to work. Conclusion: The results indicate that subacute rehabilitation with attention training (< 4 months) is preferable compared to post-acute intervention (4-12 months). There were only minor differences between the training methods.